The Initial Prototype of Innovative Science Learning Model to Improve Students’ Scientific Literacy and Support SDGs Quality Education - Muhammad Novaldy Nur Dwinanda Wahab; Wasis Wasis; Binar Kurnia Prahani; Henny Ekawati Haryono; Budi Jatmiko; Madlazim Madlazim; Muhammed Akif Kurtuluş; Muhammad Abd. Hadi Bunyamin (AMPLITUDO : Journal of Science and Technology Innovation, 2026)
Scientific literacy is a crucial component of modern science education. It encompasses the skills necessary to explain scientific phenomena, evaluate investigations, interpret evidence, and apply scientific knowledge to make informed decisions in daily life. However, many students currently lack these skills because existing models often struggle to bridge the gap between authentic real-world phenomena and interactive learning. This research aims to develop an interactive learning model that is designed to improve student scientific literacy, named Scientific Literacy Interactive Model (SLIM). SLIM facilitates the practice of scientific literacy by engaging students with authentic real-world phenomena through an interactive learning experience that is supported by augmented-reality (AR). This study outlines the theoretical and empirical foundations of SLIM, its syntax, teacher and student activities, and the integration of AR to enhance the learning process. The proposed model consists of five syntaxes, namely authentic phenomena orientation, interactive exploration, group analysis,  seminar, and reflection. As this study is limited to the development of an initial prototype SLIM learning model, further research is required to assess the validity, practicality, and effectiveness of SLIM in a classroom setting